Ответы и объяснения

  • Участник Знаний
2013-03-16T16:51:16+04:00

Возведя в квадрат получим:

16(x^2-5x+11)=(x-2)^2*(x-3)^2

16x^2-80x+176=x^4-10x^3+37x^2-60x+36

x^4-10x^3+21x^2+20x-140=0

(x-7)(x+2)(x^2-5x+10)=0

3 cлучая

1) x=7

2) x=-2

3) x^2-5x+10=0⇒нет реш.

 

ОТВЕТ: -2 и 7

 

 

Лучший Ответ!
2013-03-16T16:57:04+04:00

4\sqrt{x^2-5x+11}=(x-2)(x-3)\\ 4\sqrt{x^2-5x+11}=(x^2-5x+6)\\ 16(x^2-5x+11)=(x^2-5x+6)^2\\ x^2-5x=a\\ 16(a+11)=(a+6)^2\\ 16a+176=a^2+12a+36\\ a^2-4a-140=0\\a_1=14\\a_2=-10\\ x^2-5x=14\\ x^2-5x-14=0\\ x_1=-2\\x_2=7\\x^2-5x=-10\\x^2-5x+10=0\\D<0

Проверка:

х=-2,   4+10+11=25>0

x=7,    49-35+11=25>0

-2*7=-14

Ответ: -14